Energy advantages of application of steam compressor heat pumps with electric and cogeneration drives - Ostapenko, Olga; Leshcnenko, Vadym; Tikhonenko, Roman (Scientific Works of Vinnytsia National Technical University, 2015)
Energy advantages of steam compressor heat pumps (HP) with electric and cogeneration drives has been considered. The presented results of research allow to evaluate the economy of equivalent fuel due to application of steam compressor heat pumps (HP) with electric and cogeneration drives for various operation modes of HP and enable to select efficient operation modes of steam compressor HP taking into account the impact of the sources of drive energy of steam compressor HP and taking into consideration energy losses of the process of generation, supply and transformation of electric energy. REFERENCES 1. Исанова А. В. Повышение эффективности и выбор рациональных параметров и режимов работы теплона- сосных станций для систем отопления и горячего водоснабжения : автореферат дисс. … канд. тех. наук : 05.23.03 / Исанова Анна Владимировна. – Воронеж, 2011. – 18 с. 2. Денисова А. Є. Аналіз парокомпресійного циклу теплонасосних станцій теплопостачання / А. Є. Денисо- ва., В. Ю. Бірюк // Тр. Одес. политехн. ун-та. – 2012. – Вып. 1 (38). – С. 125 – 128. 3. Безродний М. К. Термодинамічна ефективність теплонасосних схем теплопостачання / М. К. Безродний, Н. О. Притула // Вісник ВПІ. – 2013. – № 3. – С. 39 – 45. 4. Ильин Р. А. Новый подход к оценке эффективности тепловых насосов / Р. А. Ильин, А. К. Ильин // Вест- ник АГТУ. Сер.: Морская техника и технология. – 2010. – № 2. – С. 83 – 87. 5. Елистратов С. Л. Комплексное исследование эффективности тепловых насосов : дисс. ... докт. техн. наук : 01.04.14 / Елистратов Сергей Львович. – Новосибирск, 2010. – 383 с. 6. Energy efficiency of steam compressor heat pumps with electric and cogener ation drive [Електронний ресурс] / О. P. Оstapenko, V. V. Leshchenko, R. O. Tikhonenko // Scientific Works of Vinnytsia National Technical University. – № 4. – 2014. – Режим доступу до журн.: http://praci.vntu.edu.ua/article/view/3821/5564. 7. Калнинь И. М. Техника низких температур на службе энергетики / И. М. Калнинь // Холодильное дело. – 1996. – № 1. – С. 26 – 29. 8. Ткаченко С. Й. Парокомпресійні теплонасосні установки в системах теплопостачання. Монографія / С. Й. Ткаченко, О. П. Остапенко. – Вінниця: УНІВЕРСУМ-Вінниця. – 2009. – 176 с.